AKUNTABILITAS PUBLIK DALAM PENGADAAN BARANG/JASA PEMERINTAH SECARA ELEKTRONIK (E-PROCUREMET) DI PEMERINTAH PROVINSI LAMPUNG - Achmad Suharyo; Sukismanto Aji; Christopan Deswansyah (Universitas Bandar Lampung (UBL), 2021)
The objective of this study is to investigate the public accountability of the online procurement of good and services at Lampung Government. This study uses dimensions of transparency, liability, control, responsibility, and responsivity. Object of this research is the procurement of goods and services electronically at the LPSE and ULP Unit of the Lampung Provincial Government. This type of research is a case study. This research uses a qualitative approach. The research data were obtained through interviews, observation, and documentation study. The results showed that public accountability with the application of EProcurement in Lampung Province in the aspect of achieving goals, generally has been going well and has a significant effect on changes in the process of procuring goods / services. The process of procuring goods / services is more efficient, effective, open and competitive, transparent, fair / non-discriminatory, and accountable.